Do different vertical positions of maxillary central incisors influence smile esthetics perception? - Erica Bretas Cabral Menezes; Marcos Alan Vieira Bittencourt; Andre Wilson Machado (Dental Press Journal of Orthodontics)
ABSTRACT INTRODUCTION: The purpose of this study was to determine the perception of smile esthetics among orthodontists and layperson, with respect to different maxillary central incisors vertical positions in full-face and close-up smile analyses. METHODS: Frontal photographs of the smiles of two adult women were used. Images were altered to create a symmetrical image with the gingival margin levels of the maxillary canines matching the central incisors and a 1.0-mm central-to-lateral incisal step. Later, the images were altered in order to create six different central incisor vertical positions in 0.5-mm increments. The images were randomly assembled in an album, which was given to 114 judges, 57 orthodontists and 57 laypersons, who were asked to evaluate the attractiveness of the images using the visual analog scale. The data collected were statistically analyzed by means of 1-way analysis of variance with the Tukey post-hoc test and the Student t test. RESULTS: The highest rated smiles showed two notable characteristics: a) the central incisor gingival margins matched or were 0.5 mm below the line of the canine gingival margins and; b) the central-to-lateral incisal step was 1.0 to 1.5 mm. The worst smiles showed two notable characteristics: a) the central incisor gingival margins were 1.0 mm above or 1.5 mm below the canine gingival margins and; b) no step between the centrals and laterals or a 2.5-mm step. CONCLUSION: The vertical position of the maxillary central incisors significantly affected the perception of the smile esthetics, whereas slightly extruded central incisors were more esthetically preferred than intruded.